After the “Clash”: Assessing the Cultural Repercussions of Globalization in Developing Nations in the Twenty-First Century. - Bandopadhyay, Saptarishi (2005)
The paper deals with how an imbalanced flow of information through modern technology (like broadcasting satellites and the Internet) is affecting culture especially in the developing nations. This issue is one that needs to be seriously considered by nations in the background of the growing polarization of the world along ethnic and cultural fault lines. The paper considers the future of world politics a decade after Huntington’s “Clash of the Civilizations…” and insists that the entrance of diverse globalization and pervasive communication technology necessitates that we drop the standard political measures of grading cultural and social change and adopt methodologies along the lines of homogenization, polarization and hybridization which are better equipped to describe the present day cultural conflict as well as humanity’s best bet for the future.